Synthesis and characterization of metal free and metal phthalocyanines bearing thymol moieies derived from antimicrobial and antifungal terpenoids - Atajanov, Rovshen (My University, 2020)
Ftalosiyaninler (Pcs), 18 tane delokalize π elektronuna sahip tetrapirol makrohalkalı bileşikler olup, doğal bileşikler olan porfirinlerin sentetik türevleridir. Kimyasal ve fiziksel dayanıklılıklarının yanı sıra tasarım esneklikleri ve geniş spektroskopik özellikleri, sentezlerinden bu yana kimyagerlerin, fizikçilerin ve endüstriyel bilim insanlarının ilgisini çekmektedir. Pc halkasının aksiyal veya periferal konumlarında yapılan değişiklikler bu bileşiklere çok geniş yelpazede fiziksel ve kimyasal özellikler kazandırabilir [1].Timol, monoterpenoid sınıfı fenol bileşiklerinden olup Thymus vulgaris, Monarda puctata [2] ve birçok farklı bitkilerin esansiyel yağlarından elde edilir. Timol, kanser hücrelerine [3] ve mikrobiyal hastalıklara [4] karşı geniş bir aktivite göstermekle beraber, anti oksidatif [6] ve iltihaplanmaya karşı [5] etkileri vardır.Bu çalışmada, timol ve ftalonitril bileşikleri arasında nükleofilik sübstitüsyon ve azo kenetleme reaksiyonları gerçekleştirilmiştir. Bu reaksiyonlardan elde edilen bileşiklerden, fiziksel ve kimyasal özelliklerine göre potansiyel kullanım alanlarını incelemek üzere metalli ve metalsiz Pc bileşikleri sentezlenmiştir. Ayrıca, bazı bileşiklerin Fotodinamik Terapi (PDT) çalışmaları için, fotofiziksel ve fotokimyasal özellikleri araştırılmıştır.Sentezlenen yeni bileşiklerin yapıları FT-IR, UV-vis, NMR ve MALDI TOF MS gibi metotlarla analiz edilmiş ve aydınlatılmıştır.Bu tez boyunca Pc’lerin moleküler materyaller arasında en çok yönlü ve ilginç bileşikler olduğu gösterilmiştir. Bu bileşiklere dayanan teknolojik uygulamalar halihazırda piyasada mevcut olsa da spesifik uygulamalar için uygun özelliklere sahip Pc’lerin tasarımı, bu olasılıkların iyileştirilmesi ve yeni özelliklerinin ve uygulamalarının ortaya çıkarılması amacıyla incelenmeye devam edecektir.

Phthalocyanines (Pcs) are tetrapyrrolic macrocycles with 18 delocalized π- electrons and are synthetic analogues of naturally occurring porphyrins. Along with their chemical and physical stability, their architectural flexibility and broad spectroscopic properties attract the interest of chemists, physicists and industrial scientists since the discovery of their synthesis. Modifications in axial or peripheral positions of Pc ring yield wide distribution of physical and chemical characteristics [1].Thymol is phenolic monoterpenoid compound obtained from essential oils of Thymus vulgaris, Monarda puctata [2] and various other kinds of plants. It shows wide biological activities against cancerogenous cells [3], microbial diseases [4] and also has been known to exhibit anti-inflammatory [5] and anti-oxidative effects [6].In this work, nucleophilic substitution and azo coupling reactions were carried out between thymol and phthalonitrile compounds. Using the starting compounds obtained from these reactions, new metallo- and metal-free Pcs were synthesized in order to investigate their potential applications suitable with their chemical and physical characteristics. Furthermore, photophysical and photochemical properties of some of newly synthesized Pcs were investigated for photodynamic therapy (PDT) studies.The structures of new compounds were determined based on the results of spectroscopic methods such as FT-IR, UV-vis, NMR and MALDI TOF MS.Throughout this thesis it has been shown that phthalocyanines are among the most versatile and interesting compounds within molecular materials. Although technological applications based on these compounds already exist in the market, the design of phthalocyanines with suitable properties for specific applications will continue to be studied due to the possibilities of improvement and the appearance of new properties and applications of these compounds.
Keywords: Azo; Chemistry; Chemistry, Organic; ftalosiyanin; Kimya; Kimya, Organik; PDT; phthalocyanine; sentez; synthesis; thymol; timol